Ανάλυση δεδομένων γονιδιακής έκφρασης με χρήση εμπειρικών Μπεϋζιανών μεθόδων και υπολογιστική κατηγοριοποίηση καρκινικών μελανωματικών δειγμάτων για επανατοποθέτηση φαρμάκων - Νταγιάντας, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Μηχανολογικών Κατασκευών και Αυτομάτου Ελέγχου.Εργαστήριο Εμβιομηχανικής και Συστημικής Βιολογίας, 2018)
Gene expression data for melanoma and healthy melanocyte samples from four different DNA microarrays of GEO were integrated through Bayesian model correction. Differential gene expression analysis was conducted with resampling and after the clustering of the cell lines in the space of the first two principal components. The differentially expressed genes were used as features for an SVM algorithm to classify healthy and cancerous samples, and the gene signatures of the cell lines were used as input into the cMap tool of Broad Institute to find drugs with similar signatures, for potential therapy.